Pengujian Kuat Tarik dan Kekerasan pada Alkyd Resin dari Kombinasi Palm Fatty Acid Distillate dan Urea Formaldehid Terbutilasi - Kurniawati, Mukasi Wahyu; Ulma, Zeni (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M), Politeknik Negeri Cilacap, 2024)
The utilization of polymers, particularly alkyd resin, across various industries is increasing due to its superior characteristics such as flexibility and strength. Palm Fatty Acid Distillate (PFAD) and tert-butylated urea formaldehyde are two commonly used raw materials in the production of these polymers. This study aims to evaluate the mechanical properties, particularly tensile strength and hardness, of coating materials made from a combination of PFAD-based alkyd resin and tert-butylated urea-formaldehyde. The synthesis of the resins carried out with various material composition and involves an oxalic acid as catalyst, followed by testing the tensile strength and hardness of the coating material.. The results indicate that variations in the composition of materials and the use of catalysts affect the mechanical characteristics of the materials. Changes in material composition may result in variations in tensile strength, while the use of catalysts influences the hardness of the materials. An increase in the amount of tert-butylated urea formaldehyde leads to an increase in tensile strength in some compositions, but in certain compositions, weaknesses in the bond between alkyd resin and tert-butylated urea formaldehyde result in a decrease in tensile strength. For instance, at a mole ratio of tert-butylated urea formaldehyde to butanol of 1:1, the highest tensile strength obtained was 50 MPa, while at a ratio of 2:1, the tensile strength decreased to 40 MPa.